Multi-Keyword Searchable Identity-Based Proxy Re-Encryption from Lattices - Zhuang, Er-Shuo; Fan, Chun-I (Mathematics (Basel), 2023)
To protect the privacy of cloud data, encryption before uploading provides a solution. However, searching for target data in ciphertext takes effort. Therefore, searchable encryption has become an important research topic. On the other hand, since the advancement of quantum computers will lead to the crisis of cracking traditional encryption algorithms, it is necessary to design encryption schemes that can resist quantum attacks. Therefore, we propose a multi-keyword searchable identity-based proxy re-encryption scheme from lattices. In addition to resisting quantum attacks, the proposed scheme uses several cryptographic techniques to improve encryption efficiency. First, identity-based encryption is used to reduce the computation and transmission costs caused by certificates. Second, the proposed scheme uses proxy re-encryption to achieve the purpose of outsourced computing, allowing the proxy server to reduce the computation and transmission costs of the users. Third, the proposed multi-keyword searchable encryption can provide AND and OR operators to increase the flexibility of searchability. Moreover, the access structure of the proposed scheme is not based on a linear secret sharing scheme (LSSS), avoiding the errors caused by an LSSS-based structure in decryption or search results. Finally, we also give formal security proof of the proposed scheme under the decisional learning with errors assumption.